The Idea Replacement and System Improvement of Copyright Law - Zhang, Yu (Technium Social Sciences Journal, 2022)
Copyright law is not only a law of rights but also a law of cultural development, which not only guarantees copyright but also constructs a cultural innovation system. The copyright law has the attribute of social law. From the beginning, it is necessary to build a balance mechanism between the copyright owner and the public. We must redefine the concept of public domain reservation, change the preferential protection of copyright owners, and build a balanced interest game mechanism by absorbing the effective participation of the public in the legislative process.